Engineered Breast Cancer Cell Spheroids Reproduce Biologic Properties of Solid Tumors. Issue 21 (7th September 2016) - Ham, Stephanie L.; Joshi, Ramila; Luker, Gary D.; Tavana, Hossein
Abstract : Solid tumors develop as 3D tissue constructs. As tumors grow larger, spatial gradients of nutrients and oxygen and inadequate diffusive supply to cells distant from vasculature develops. Hypoxia initiates signaling and transcriptional alterations to promote survival of cancer cells and generation of cancer stem cells (CSCs) that have self‐renewal and tumor‐initiation capabilities. Both hypoxia and CSCs are associated with resistance to therapies and tumor relapse. This study demonstrates that 3D cancer cell models, known as tumor spheroids, generated with a polymeric aqueous two‐phase system (ATPS) technology capture these important biological processes. Similar to solid tumors, spheroids of triple negative breast cancer cells deposit major extracellular matrix proteins. The molecular analysis establishes presence of hypoxic cells in the core region and expression of CSC gene and protein markers including CD24, CD133, and Nanog. Importantly, these spheroids resist treatment with chemotherapy drugs. A combination treatment approach using a hypoxia‐activated prodrug, TH‐302, and a chemotherapy drug, doxorubicin, successfully targets drug resistant spheroids. This study demonstrates that ATPS spheroids recapitulate important biological and functional properties of solid tumors and provide a unique model for studies in cancer research. Abstract : 3D Cancer spheroids formed with the aqueous two phase system technology at a larger density reproduce key biological properties such as collagen I expression, density dependent proliferation of only outer cells, and inner core hypoxia that correlate with drug resistance and cancer stem cell properties.